Monotonicity, Concavity, and Convexity of Fractional Derivative of Functions. (31st October 2013) - Zhou, Xian-Feng; Liu, Song; Zhang, Zhixin; Jiang, Wei
Abstract : The monotonicity of the solutions of a class of nonlinear fractional differential equations is studied first, and the existing results were extended. Then we discuss monotonicity, concavity, and convexity of fractional derivative of some functions and derive corresponding criteria. Several examples are provided to illustrate the applications of our results.